2009
DOI: 10.1111/j.1600-0560.2009.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic systemic fibrosis with a spectrum of clinical and histopathological presentation: a disorder of aberrant dermal remodeling

Abstract: NSF may present with a spectrum of clinical abnormalities, and exhibit overlapping histopathological features resembling cicatrix and other dermal reparative/regenerative processes. NSF may in fact to be a disorder of aberrant extracellular matrix remodeling in patients with renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Taken together, our findings suggest that a process of aberrant reparative process is occurring in the skin lesions of patients with NSF 11 . This reparative process can be seen in the findings of accumulation of collagen and elastin (‘elastocollagenous balls'), sclerotic collagen bodies as well as areas of osseous metaplasia in skin biopsies of patients with late‐stage NSF.…”
Section: Discussionsupporting
confidence: 53%
“…Taken together, our findings suggest that a process of aberrant reparative process is occurring in the skin lesions of patients with NSF 11 . This reparative process can be seen in the findings of accumulation of collagen and elastin (‘elastocollagenous balls'), sclerotic collagen bodies as well as areas of osseous metaplasia in skin biopsies of patients with late‐stage NSF.…”
Section: Discussionsupporting
confidence: 53%
“…NSF is undeniably a rare but devastating disease, presenting with a spectrum of clinical and histopathologic manifestations (2,3). It is associated with increased tissue deposition of collagen in the skin, subcutaneous fascia, striated muscles, joints, diaphragm, lungs, liver, and myocardium (4).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been a few case reports in which exposure to GBCA could not be confirmed from patients' medical records [43]. Recently, Deng et al [44] reported seven NSF patients; although six patients had no known exposure history to GBCA, tissue gadolinium levels tested for three of these patients were significantly increased compared with normal tissue, supporting the association of GBCA and NSF. Without examining affected tissue for the presence of gadolinium, a history of exposure to GBCA cannot be excluded with certainty, since documentation of contrast media use is often inadequate [45].…”
Section: Discussionmentioning
confidence: 94%